Cell electropermeabilization to small molecules in vitro - Maček Lebar, Alenka (Radiology and oncology (Ljubljana), 2001)
A systematic study concerning the role of the different electric field parameters (pulse number, duration and amplitude) on electropermeabilization of DC3F cells to small molecules (propidium iodide) and on cell viability is presented. Cell permeabilization and viability dependence on the pulse amplitude was determined by twenty different sets of electrical parameters. The number of pulses varied between 1 and 64 and pulse duration between 20 micros and 1 ms. The most important parameter was the pulse amplitude because at triggered the electropermeabilization process and the process of cell death. Either in the case of electropermeabilization as well as in the case ofcell viability experiments, the parameter Uso (the pulse amplitude leading to permeabilization or to the death of 50% of cell population) was not changedif the set of electrical parameters consisted of more than 16 pulses. This was independent of the pulse duration. The efficiency of permeabilizationwas enhanced by using of longer pulses. Such a systematic study of the influence of different electric field parameters on electropermeabilization and cell viability may serve as a base for optimization of the electropermeabilization conditions for different applications.
Keywords: biomedicina; celice; Cell survival; Electromagnetic fields; Electroporation; elektrofiziologija; Fibroblasts; fiziologija; preživetje; Propidium